NURSING CARE IN DISEASES OF THE NOSE AND PARANASAL SINUSES - Tadjibayeva Axila Mamirjanovna; Yergasheva Navro'za Nigmatulla qizi (Modern American Journals, 2025)
Diseases of the nose and paranasal sinuses, such as rhinitis, sinusitis, nasal polyps, and allergic conditions, are among the most common disorders encountered in clinical practice. They not only impair patients’ quality of life but also, if untreated, may lead to complications such as chronic infections and respiratory dysfunction. Nursing care plays a crucial role in the prevention, treatment, and rehabilitation of these conditions. Nurses are responsible for patient education, medication administration, monitoring of symptoms, and ensuring adherence to prescribed treatment regimens. They also provide supportive care during surgical interventions, such as functional endoscopic sinus surgery (FESS), and in postoperative recovery. Modern nursing approaches emphasize holistic care, which includes physical, psychological, and social support for patients. By integrating evidence-based practices, nurses contribute to faster recovery, reduced recurrence rates, and improved overall patient outcomes.
Keywords: Nursing care, nose diseases, paranasal sinuses, rhinitis, sinusitis, nasal polyps, allergic rhinitis, patient education, postoperative care, evidence-based practice.